Associations of the activity and concentration of carbonic anhydrase VI with susceptibility to dental caries: A systematic review and meta‐analysis - Rania Al‐Mahdi; Hesham Al‐Sharani; Mohammed Al‐Haroni; Esam Halboub (Wiley, 2023)
Abstract Objectives A number of studies have claimed that carbonic anhydrase VI (CA VI) is associated with dental caries. The aim of this systematic review and meta‐analysis was to systematically review and analyze the literature on the association of CA VI (in terms of concentration and activity) with dental caries. Materials and Methods A systematic review was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) guidelines. Relevant search terms were employed to search the following databases: PubMed, Web of Science, Scopus, China National Knowledge Infrastructure (CNKI), and Cochrane Library databases. Eligible publications from inception to August 2022 were included. The relevant records were assessed independently by two reviewers, and a meta‐analysis was performed using RevMan 5.3. Results Out of 237 relevant records from the initial search, 9 met the criteria for this review. The 9 papers, including 477 participants, were qualitatively analyzed. Seven studies with 411 participants (203 caries‐free) were included in the meta‐analysis on CA VI activity, and 2 studies with 141 participants (71 caries‐free) were included in the meta‐analysis on CA VI concentration. The results showed that CA VI activity was significantly higher among participants with caries than their caries‐free counterparts (standardized mean difference (SMD) = 0.894, 95% confidence interval (CI95%): 0.386 and 1.392; p < 0.001), whereas the CA VI concentration was significantly lower among participants with caries than their caries‐free counterparts (SMD = −0.672, CI95%: −1.011 and −0.332; p < 0.001). Conclusions This meta‐analysis of a relatively small number of studies suggests that the CA VI concentration is lower and CA VI activity is higher in patients with dental caries than in caries‐free individuals; however, further studies are needed to determine the exact role of CA VI in dental caries.